Innovacionnye technologii v trenirovocnom processe edinoborcev (po dannym zarubežnoj literatury - Aranson, M. V.; Ovcharenko, L. N.; Ozolin, E. S.; Tuponogova, O. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The analysis of foreign scientific literature devoted to the planning and control of training in Greco-Roman wrestling, taekwondo and fencing has been carried out. It is revealed that scientists pay great attention to the improvement of strength training methods, since speed-strength qualities are one of the main components of the preparedness of a single combatant. It is also important to monitor performance, including changes in body composition. Specific tests are developed that allow you to quickly determine the changes in general and special preparedness of an athlete. The training process often introduces additional components that increase its effectiveness, such as relaxation. These points should be taken into account when planning research for the development of training methods in martial arts.